The insecticidal activity and repellency of the Andira paniculata (Fabaceae) extract against Sitophilus zeamais (Coleoptera: Curculionidae) (Revista Brasileira de Plantas Medicinais, 2025)
Sitophilus zeamais is among the main pests affecting stored maize grains. The aim of the current study is to assess the mortality and repellency of organic extracts from Andira paniculata leaves against maize weevil, Sitophilus zeamais. The experiments were conducted at the Agricultural Entomology Laboratory of Instituto Federal Goiano – Urutaí Campus. A completely randomized experimental design was adopted to assign the mortality and repellency in 17 treatments in four replications. Andira paniculata leaves were oven dried, grounded and subjected to exhaustive extraction using ethanol. Hexane (APFE-H), Dichloromethane (APFE-D), Ethyl Acetate (APFE-A) and Hydroalcoholic (APFE-W) extracts were used at the concentrations 0.01%, 0.1%, 0.5% and 1 %, respectively. BIOMATRIX BM 3061 hybrid grains were treated with the plant extracts and, subsequently, infested with Sitophilus zeamais. The mortality was assessed 24, 48 and 72 hours, as well as 30, 60 and 90 days after exposed to the plant extracts. The ethyl acetate (1.00%) showed the  highest mortality (95%). The ethyl acetate (0.01 - 0.5%) also showed the similar performance after 48 hours in the repellency test. Dichloromethane presented the lowest LD50 (0.2115%), and showed a highest mortality of Sitophilus zeamais. Thus, Andira paniculata has potencial for future studies on the control of Sitophilus zeamais in stored maize grains.